2007
DOI: 10.1155/2008/234563
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Quality of Water in Some Streams of Cauvery River

Abstract: The quality of water in four streams of Cauvery River in Mandya District, where many small scale sugar and brewery distilleries are located, was analysed. Sampling was carried out from four streams designated as station 1 (upstream of effluent discharge point), station 2 (effluent discharge point) and station 3 (downstream of effluent discharge) station 4 (fresh water stream) to assess the impact of effluent on the water quality. The river water composition is increasingly dominated by Na and Cl in the downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…The P H of water body can be changed with the change of season [25,33], as there are several factors which govern it directly or indirectly are changed with the change of season. The P H of surface water increases with the increase of photosynthesis by autotrops as they use dissolved CO 2 and release O 2 to the surface of water and low P H at the bottom of the surface of water is due to the liberation of acids and CO 2 from the decomposition organic maters under low O 2 concentration [10,21,25,28]. The dissolution of CO 2 and Cl 2 in the surface of water forms carbonic acid and hypochlorous acid respectively which fall the P H [40,42].…”
Section: :-mentioning
confidence: 99%
See 1 more Smart Citation
“…The P H of water body can be changed with the change of season [25,33], as there are several factors which govern it directly or indirectly are changed with the change of season. The P H of surface water increases with the increase of photosynthesis by autotrops as they use dissolved CO 2 and release O 2 to the surface of water and low P H at the bottom of the surface of water is due to the liberation of acids and CO 2 from the decomposition organic maters under low O 2 concentration [10,21,25,28]. The dissolution of CO 2 and Cl 2 in the surface of water forms carbonic acid and hypochlorous acid respectively which fall the P H [40,42].…”
Section: :-mentioning
confidence: 99%
“…The comparatively lower P H in the month of May can be attributed due to low flow of water and decomposition of organic materials at high temperature that releases acids and CO 2 [20,25,35,61,63]. The higher P H in rainy(August) and post-rainy(October) for entire two years of study can be due to high rate of photosynthesis by autotrops as myxophyceae bloom is observed in the river bed, high flow of rain water and flood that dilutes the pollutants [10,20,23,35,42,44,70]. ) and April for the two years of the study may be due to the decomposition of organic materials and other waste materials thrown off by the large number of picnic parties to the river bed [27,44] as because Hadagada is a famous picnic spot and attracts large number picnic parties to hold picnic here from the month of December to February in every year, as reported in daily "Samaj" on 12.12.2016.…”
Section: :-mentioning
confidence: 99%
“…Due to heavy reflux of sewage in TD-7 drainage canal the BOD values were observed 97-305 mg/l at Turkey [23]. [24] observed low level of BOD indicating less pollution status of river Cauvery. The value of BOD in the present study was higher on site II as compared to Site I.…”
Section: A Physico-chemical Parametersmentioning
confidence: 99%
“…Shyamala et al [5] found pollution at the banks of Cauvery River and Kalingarayan canal in and around Erode town, Tamilnadu. The study showed increased in the pollution load due to the movement of fertilizers, agricultural ashes, industrial effluents and anthropogenic wastes at river Cauvery [6]. Tripathi et al [7] found degradation in water quality of River Rapti near Balrampur in Uttar Pradesh.…”
Section: Introductionmentioning
confidence: 99%